2022
DOI: 10.1155/2022/1193075
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Immunotherapy Combined with Radiotherapy in Patients with Brain Metastasis of Driver Gene-Negative Non-Small-Cell Lung Cancer

Abstract: Purpose. To observe the remission rate and side effects of immunotherapy combined with radiotherapy in patients with brain metastasis of driver gene-negative non-small-cell lung cancer (NSCLC). Methods. 152 patients with NSCLC brain metastasis admitted to our hospital from January 2019 to December 2021 were selected as the research objects. Patients were divided into a single group (85 cases) and a combined group (67 cases) according to treatment methods. The therapeutic effects and side effects of the single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…We retrieved 2798 records from three databases, of which 709 duplicated records were excluded. After a series of filters, eventually, 25 journal articles 6 , 7 , 8 , 9 , 10 , 11 , 12 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 were included for the present meta‐analysis. In some articles, two or more arms of combined treatment of ICB + RT in articles were analyzed separately in our meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We retrieved 2798 records from three databases, of which 709 duplicated records were excluded. After a series of filters, eventually, 25 journal articles 6 , 7 , 8 , 9 , 10 , 11 , 12 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 were included for the present meta‐analysis. In some articles, two or more arms of combined treatment of ICB + RT in articles were analyzed separately in our meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Results of the meta‐analysis in 10 studies 6 , 7 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 comparing ICB plus RT with ICB were performed in Figure 2 , ICB combined with RT was better than without it both in short‐term and long‐term efficacy without increased toxicity. ORR, DCR, OS, and PFS were significantly inferior in patients with combination therapy ( I 2 = 0.00%, OR 1.31, 95% CI 1.13–1.52, I 2 = 0.00%, OR 1.13, 95% CI 1.02–1.26, I 2 = 42.1%, OR 0.81, 95% CI 0.72–0.92, I 2 = 34.5%, OR 0.80, and 95% CI 0.71–0.89, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%